THE TECHNOLOGY OF MILK AND DAIRY PRODUCTS - Koshkarbaeva Gulbanu Rakimovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. Automated milking systems have revolutionized the milking process by increasing efficiency and reducing labor requirements. Milk cooling and storage equipment ensure that milk is preserved at the optimal temperature to maintain its quality. Pasteurization and homogenization techniques have become standard practices in the dairy industry to eliminate harmful bacteria and create a uniform product. Processing equipment plays a crucial role in transforming milk into various dairy products such as cheese, yogurt, and butter. Packaging techniques have also advanced, with the development of aseptic packaging and innovative designs that enhance product shelf life and convenience for consumers. Quality control measures are implemented at every stage of production to ensure that milk and dairy products meet stringent safety and quality standards. Overall, these technological advancements have improved efficiency, enhanced the quality and safety of dairy products, and contributed to the growth and sustainability of the dairy industry.